ALMA uncovers the [C ii] emission and warm dust continuum in a z = 8.31 Lyman break galaxy - Bakx, Tom J L C; Tamura, Yoichi; Hashimoto, Takuya; Inoue, Akio K; Lee, Minju M; Mawatari, Ken; Ota, Kazuaki; Umehata, Hideki; Zackrisson, Erik; Hatsukade, Bunyo; Kohno, Kotaro; Matsuda, Yuichi; et al. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT We report on the detection of the [C ii] 157.7 μm emission from the Lyman break galaxy (LBG) MACS0416_Y1 at z = 8.3113, by using the Atacama Large Millimeter/submillimeter Array (ALMA). The luminosity ratio of [O iii] 88 μm (from previous campaigns) to [C ii] is 9.3 ± 2.6, indicative of hard interstellar radiation fields and/or a low covering fraction of photodissociation regions. The emission of [C ii] is cospatial to the 850 μm dust emission (90 μm rest frame, from previous campaigns), however the peak [C ii] emission does not agree with the peak [O iii] emission, suggesting that the lines originate from different conditions in the interstellar medium. We fail to detect continuum emission at 1.5 mm (160 μm rest frame) down to 18 μJy (3σ). This non-detection places a strong limits on the dust spectrum, considering the 137 ± 26 μJy continuum emission at 850 μm. This suggests an unusually warm dust component (T > 80 K, 90 per cent confidence limit), and/or a steep dust-emissivity index (βdust > 2), compared to galaxy-wide dust emission found at lower redshifts (typically T ∼ 30–50 K, βdust ∼ 1–2). If such temperatures are common, this would reduce the required dust mass and relax the dust production problem at the highest redshifts. We therefore warn against the use of only single-wavelength information to derive physical properties, recommend a more thorough examination of dust temperatures in the early Universe, and stress the need for instrumentation that probes the peak of warm dust in the Epoch of Reionization.